LncRNA MCM3AP-AS1 inhibits cell proliferation in cervical squamous cell carcinoma by down-regulating miRNA-93 - Lan, Liu (Biosci Rep, 2020)
Background: MCM3AP antisense RNA 1 (MCM3AP-AS1) is characterized as an oncogenic lncRNA in hepatocellular carcinoma and glioblastoma. We analyzed TCGA dataset and observed the down-regulation of MCM3AP-AS1 in cervical squamous cell carcinoma (CSCC). The present study was therefore performed to investigate the role of MCM3AP-AS1 in CSCC. Methods: A total of 64 female patients with CSCC (38–68 years old; mean age: 53.1 ± 6.5 years old) were enrolled in the present study. RT-qPCR was performed to evaluate gene expression. Methylation specific PCR (MSP) was performed to assess the methylation of miR-93 gene after the overexpression and silencing of MCM3AP-AS1. Cell transfections were performed to investigate the interactions between MCM3AP-AS1 and miR-93. Cell proliferation was assessed by CCK-8 assay. Results: The results showed that MCM3AP-AS1 was down-regulated in CSCC and predicted poor survival. The expression levels of MCM3AP-AS1 were inversely correlated with the expression levels of miR-93. Overexpression of MCM3AP-AS1 led to down-regulation of miR-93, while silencing of MCM3AP-AS1 played an opposite role in CSCC cells. Methylation-specific PCR revealed that MCM3AP-AS1 could positively regulate the methylation of miR-93 gene. Cell proliferation analysis showed that overexpression of MCM3AP-AS1 led to reduced proliferation rate of CSCC cells. Silencing of MCM3AP-AS1 played an opposite role and overexpression of miR-93 reduced the effects of overexpressing MCM3AP-AS1. Conclusions: Therefore, MCM3AP-AS1 may inhibit cell proliferation in CSCC by down-regulating miRNA-93.